Laparoscopic Repair of a Left Retrocaval Ureter in a 16-Year-Old Girl - Anna Kadar; Lorena Vatra; Anca Avram; Daniela Stoica; Marcel Oancea (European Journal of Pediatric Surgery Reports, 2018)
Left retrocaval ureter is an extremely rare congenital malformation which is associated with situs inversus, duplicated or translated inferior vena cava (IVC). We report a female adolescent who presented with a history of intermittent, colicky lumbar pain. Diagnostic workup revealed left retrocaval ureter and left ureterohydronephrosis. The girl underwent laparoscopy. The renal pelvis and ureter posterior to the vena cava were dissected, transected at the caudal point of the dilated ureteral segment, and uncrossed and repositioned lateral to the vena cava. Ureteroureterostomy was performed over a double-J ureteral stent after spatulation of the distal ureter. The postoperative course was uneventful and the ureteral stent removed after 5 weeks. During follow-up, the patient is symptom-free. Our case demonstrates that our laparoscopic approach is feasible in this rare anatomic anomaly.